2012
DOI: 10.2478/v10032-012-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Living Mulches on Selected Soil Structure Indicators in Eggplant Cultivation

Abstract: SummaryConducted research involved evaluation of selected soil properties in eggplant cultivation with the use of living mulches from white clover and perennial ryegrass. The mulching species were sown three weeks before eggplant planting, in the term of planting and three weeks after planting this vegetable. In half of August there was assessed stability of soil aggregates on the basis of the following indicators of: cloddiness (B), misting (S), structure (W) of the soil and mean weighed diameter of aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…For example, Adamczewska-Sowińska et al [11] reported that white clover increased the yield of tomato, although it needed to be periodically mowed in order to avoid competition with the crop. In addition, Wojciechowski et al [12] reported positive effects of living mulch with white clover and perennial ryegrass on soil structure in terms of stability of soil aggregates. White clover has been reported to increase arbuscular mycorrhiza and yield of corn, because its living mulch acts as a host plant for these organisms in winter [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Adamczewska-Sowińska et al [11] reported that white clover increased the yield of tomato, although it needed to be periodically mowed in order to avoid competition with the crop. In addition, Wojciechowski et al [12] reported positive effects of living mulch with white clover and perennial ryegrass on soil structure in terms of stability of soil aggregates. White clover has been reported to increase arbuscular mycorrhiza and yield of corn, because its living mulch acts as a host plant for these organisms in winter [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Számos pozitív hatásuk ismeretes, pl. a talaj megfogásával és a bolygatás, azaz a kapálás elmaradásával csökkenthetik az eróziót (Hartwig, 1988;Hartwig-Hoffmann, 1975), növelik a talaj szervesanyag tartalmát (Leary-DeFrank, 2000) ezzel javítják a szerkezetét (Wojciechowski et al, 2012) is. Ha a választott élőmulcs növényünk pillangósvirágú faj, akkor a talaj nitrogéntartalmának növekedésére is számíthatunk (Frye et al, 1985).…”
Section: Bevezetésunclassified